2018
DOI: 10.3390/su10082781
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Sustainable Supply Chain Performance—Evidence from a Developing Country, Malaysia

Abstract: Malaysia has recently started to adopt sustainable business best practices to benefit companies, environment and stakeholders. Therefore, this study demonstrates pathways to sustainable supply chain triple bottom line performance derived from linkages of institutional pressures (IP) and organizational identity (OI) to environment and social sustainable practices. It shows that the superordinate goal of sustainable supply chain management is met in spite of unyielding external pressures and desirable OI driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 96 publications
(149 reference statements)
1
28
0
Order By: Relevance
“…According to the path coefficient derived from the initial model testing, the p -value of the path from TF to B is 0.850 (see Table 4 ), indicating that the path is not significant [ 106 ]. Similar analysis procedures were conducted with the updated model.…”
Section: Resultsmentioning
confidence: 99%
“…According to the path coefficient derived from the initial model testing, the p -value of the path from TF to B is 0.850 (see Table 4 ), indicating that the path is not significant [ 106 ]. Similar analysis procedures were conducted with the updated model.…”
Section: Resultsmentioning
confidence: 99%
“…The results from the ANOVA are presented in Table 4. Normally, it is suggested that there is high degree of difference between the tested groups if the p -value of a variable is less than 0.05 [72]. In Table 4, F represents the group square difference value of F test, and Sig.…”
Section: Resultsmentioning
confidence: 99%
“…Many eminent scholars have corroborated that the inclusive environment practices make the organization more innovative, competitive, socially responsible, proactive, which works on the path of generating optimistic opportunities for its stakeholders and society leading to better performance outcomes (Reuter et al, 2004;Ketchen and Hult, 2007). Hence, the study is the demonstration of the significance of applying sustainable supply chain practices to achieve the Triple Bottom Line performance, which is the outcome of some functional constructs to the environment and stakeholders as well as the implementation of sustainable initiatives (Thong and Wong, 2018). The research work has recalled the functional adoption constructs, which are precisely dealt with by the organizations to line the adoption of sustainable supply chain practices (in the short run) and yield organizational performance (in the long term) has been expressed in the form of the following Figure 2.…”
Section: Ieos Model For Sustainable Supply Chain and Overall Organizational Performancementioning
confidence: 87%
“…The directions of work have been changed, and the vision is more inclusive now for the benefit of the entire system. In the words of Thong and Wong (2018), the economic gains earned through the adoption of social and environmental practices are salvaged by its performance results. In the words of Golicic and Smith (2013), the environmental actions are not to be profound as an end in itself rather they act as significant means to enhance the operational and financial performance of the organization and lead to the continuation of the business as well.…”
Section: Ieos Model For Sustainable Supply Chain and Overall Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation